Corrosion Rate Analysis and Remaining Life Assessment of Structural Steel in Palm Oil Mill (POM) Environment at Tanjung Seumantoh - Muhammad Zulfri; Nazaruddin Abdul Rahman; Andre Mahessa; Muhammad Isra (JURUTERA - Jurnal Umum Teknik Terapan, 2023)
Machines are tools used to simplify work processes. Within a machine, there are several main components that form the framework for its construction. These components must possess strong qualities in order to perform their functions effectively, one of which is the use of steel. Steel is a commonly utilized material in various sectors, including factories. An example of this can be seen in palm oil mills, where numerous components such as wall pipes, generating pipes, and heat pipes are made from steel. However, steel has a tendency to corrode, which can reduce its strength and shorten the lifespan of steel components. Therefore, it is crucial to calculate the remaining life of each pipe as a preventive measure. The calculation results indicate that the remaining life of the wall pipe is approximately 32 years, while the generating pipe has around 29 years, and the heater pipe has about 11 years of remaining life. In this case, the wall pipe has the longest remaining life, whereas the heater pipe has the shortest due to its continuous exposure to heat. The purpose of this research is to analyze the corrosion rate and remaining life of components made from steel materials, such as wall pipes, generating pipes, and heat pipes, in order to prevent damage caused by corrosion in palm oil mills.